A capacity allocation model for source-side shared energy storage considering multiple typical scenarios - YAN Limei; HU Jianan; ZHAO Shuqi (Zhejiang dianli)
Traditional energy storage models for renewable energy stations incur high costs， while shared energy storage can reduce construction and operational expenses and enhance economic benefits. Based on this， a robust optimization model for shared energy storage considering renewable energy output uncertainty and multiple typical scenarios is established. First， with the objective of minimizing operational costs， a capacity allocation model for shared energy storage incorporating operational control is developed. A scenario summation mechanism is introduced into the nested column-and-constraint generation （Nested C&CG） method to solve the optimization model and obtain the maximum alliance benefits. Then， the alliance benefits under various station combinations are calculated. Based on the Shapley value， the allocation benefits for each station are determined according to their contribution to the total alliance benefits， ensuring fair distribution of profits. Finally， a simulation analysis is conducted using a renewable energy station cluster in Xinjiang， China， as an example， to derive the shared energy storage configuration and operational plan. The impact of renewable energy output uncertainty on the configuration results is also analyzed. Experimental results demonstrate that the proposed shared energy storage model can effectively increase the benefits of renewable energy station clusters and has high practical application value.